Sustainable Branding and Green Marketing Strategies: Engaging Eco-Conscious Consumers and Building Responsible Brand Equity Across Emerging and Developed Economies (Journal of Asian Development Studies, 2025)
The research aimed to examine whether green marketing campaigns are effective in promoting brand loyalty, brand equity, consumer perceptions, consumer trust, and purchase intent in both emerging and developed economies. The methodology employed is a combination of quantitative and qualitative data, utilising both consumer surveys (n=600) and qualitative analysis of corporate sustainability reports in the two market settings to assess the impact of eco-labelling, sustainability reporting, and corporate social responsibility (CSR) programs on consumer behaviour in these settings. It has been analysed that there is a significant disparity between the new and established economies, where consumers in these developed economies have an enhanced sense of trust and loyalty, as well as a higher level of purchase intention for brands that are engaging in green marketing activities. In another case, consumers in the new markets are less aware and trusting, which limits the effectiveness of the green marketing efforts. The regression model indicates that the influence of eco-labelling and sustainability reporting is more substantial in developed markets, referring to the high sensitivity of brand equity, as consumers desire a higher level of transparency and trust in endorsements that address sustainability issues. The research highlights the significance of businesses changing their green marketing policies to match regional market situations, as the author emphasises the importance of transparency and authenticity in developing economies to instil confidence and enhance brand capital. The research can contribute to the existing literature on sustainable branding and provide marketers with valuable insights on identifying newly environmentally conscious buyers in global markets.